POLITIK HUKUM PEMBERLAKUAN SYARI’AT ISLAM DI ACEH - Andani, Meri (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2022)
Aceh is one of the provinces that enjoys special treatment in a number of areas, including the formation of local political parties and the implementation of Islamic Sharia. In Aceh, the execution of Islamic law is inextricably linked to legal politics, both in terms of formulation and design as well as enforcement and implementation. The current legal politics in Aceh, and even back then, cannot be divorced from the history of progress over time, beginning with the old order era and ending with the Reformation. The execution of Islamic law in Aceh did not exist at the time of Indonesian independence until the reformation phase championed by Duad Berueh began to emerge. Starting from the old order, the road of legal politics in the implementation of Islamic law in Aceh has been protracted. During the new order, the reformation period, and finally the Mou Helsinki accord. As a result, the voyage of legal politics in the implementation of Islamic law in Aceh will be described in this paper.